(untitled) (Journal of Asian Development Studies, 2017)
Here we examine the relationship between board structure (non-executive directors, executive directors and independent non-executive directors) and CEO compensation, in the context of an emerging and developing economy of Pakistan in the year 2009. Most of the previous studies that have addressed board structure and CEO compensation are based in developed economies, whereas this study focuses on the developing and emerging economy of Pakistan, which is therefore likely to make a useful contribution to the literature. The study included data from 86 listed firms of the Lahore stock exchange. The findings show that board size and percentage of independent non-executive directors have a negative relation but insignificant effect upon CEO compensation. Other variables, such as percentage of non-executive directors and percentage of executive directors, had a positive relation but these variables also did not significantly affect CEO compensation in Pakistani companies. Given the majority of firms in Pakistan are family-owned, we propose that family CEOs are likely to have power over the selection of board members, and also that the CEO, as well as the management of the firm, hold accurate information about the business. Therefore, there is an absence of an agency problem between the CEO and the board, which is responsible for reducing the independence of the board.